Molecular Mechanisms of Preeclampsia - Hod, Tammy (Cold Spring Harb Perspect Med, 2015)
Preeclampsia is a pregnancy-specific disease characterized by new onset hypertension and proteinuria after 20 wk of gestation. It is a leading cause of maternal and fetal morbidity and mortality worldwide. Exciting discoveries in the last decade have contributed to a better understanding of the molecular basis of this disease. Epidemiological, experimental, and therapeutic studies from several laboratories have provided compelling evidence that an antiangiogenic state owing to alterations in circulating angiogenic factors leads to preeclampsia. In this review, we highlight the role of key circulating antiangiogenic factors as pathogenic biomarkers and in the development of novel therapies for preeclampsia.